Pore Fluid Evolution Influenced by Volcanic Activities and Related Diagenetic Processes in a Rift Basin: Evidence from the Paleogene Medium-Deep Reservoirs of Huanghekou Sag, Bohai Bay Basin, China - Zhongheng Sun; Hongtao Zhu; Changgui Xu; Xianghua Yang; Xiaofeng Du; Qingbin Wang; Jinyang Qiao (Geofluids)
Volcanic activities exert a significant influence on pore fluid property and related diagenetic processes that substantially controlled reservoirs quality. Analysis of Paleogene medium-deep sandstones on the Huanghekou Sag provides insight into relating the diagenetic processes to pore fluid property evolution influenced by volcanic activities. Three distinct types of pore fluids were identified on the basis of an integrated and systematic analysis including core and thin section observation, XRD, SEM, CL, and trace element. Alkaline aqueous medium environment occurred in E2s1+2 where volcanic activities have insignificant influence on pore fluids, evidenced by typical alkaline diagenetic events such as K-feldspar albitization, quartz dissolution, feldspar dissolution, and carbonate cementation. During the deposition of E3d3, influx of terrestrial freshwater and alteration of ferromagnesian-rich pore water result in the formation of mixing aqueous medium environment through volcanic eruption dormancy causing zeolite dissolution, clay mineral transformation, and K-feldspar albitization. Ferromagnesian-rich aqueous medium environment developed resulting from the intensive hydrolysis of the unstable ferromagnesian minerals formed due to intense volcanic activities during E3d1+2 and corresponding predominant diagenetic processes were characterized by the precipitation and dissolution of low-silica zeolites. Therefore, the differential properties of pore fluids caused various diagenetic processes controlling reservoir quality.